Bioflocculant Technology Implementation Using Navicula sp for Harvesting of Arthrospira Platensis Culture - Suyono, Eko Agus; Satriayudistira, Jody Ashrib; Baihaqi, Yahya; Amelia, Ria (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Bioflocculation, a microalgae harvesting method utilizing organisms likebacteria and microalgae as flocculant agents, necessitates careful selectionand ratio determination of bioflocculant agents. This study seeks to ascertainthe optimal balance of bioflocculant, Navicula sp., for metabolite productionand harvesting efficiency in Arthrospira platensis culture. Spanning three oneweek cultivation stages, the research commences with A. platensis cultureunder varying salinities (0, 15, 25, and 35 ppt) in the first stage, followed bypH variations (9, 10, 11, and 12) in the second stage. The optimal salinity-pHcombination identified in the first two stages is applied in the third stage,involving bioflocculant addition to culture and medium solutions at varyingratios (0.25:1, 0.5:1, 0.75:1, and 1:1 v/v). Precipitation efficiency andpigmentation were measured using spectrophotometry, while lipid contentwas determined by the Bligh Dyer extraction method. Carbohydrate contentwas assessed using the Phenol-Sulphuric Acid assay, and protein contentwas quantified using the Bradford protein assay. The findings indicate salinity,pH, and bioflocculant influence A. platensis growth, metabolite production,and harvesting efficiency. Optimal outcomes are achieved at 15 ppt salinity,pH 9, and a 1:1 ratio of bioflocculant, yielding 1.18x10-3 g of dry biomass,3.56x105 cells/mL of cell density, 2.9x100 g/L of carbohydrates, 3.63x100 g/Lof lipids, 9.97x10-3 mg/L of chlorophyll a+b, 8.71x10-1 mg/L of carotenoids,and 3.04x10-1 g/L of protein. These results suggest that salinity addition, highpH, and the addition of Navicula sp. as bioflocculant increase the harvestingprocess efficiency of A. platensis culture.